Pengetahuan, Vulva Hygiene PERBEDAAN PENGETAHUAN TENTANG VULVA HYGIENE MASA NIFAS PADA PRIMIPARA DAN MULTIPARA DI PUSKESMAS JAGIR SURABAYA: KNOWLEDGE OF DIFFERENCE OF VULVA HYGIENE ON CHILDBIRTH IN PRIMIPARA AND MULTIPARA IN PUSKESMAS JAGIR SURABAYA - Hastuti, Puji (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2017)
Abstract Many mothers are more concerned with the baby condition rather than cleanliness vulva Hygine, it can be seen when mothers do stitching control to hospital and found in a state of less clean and moist. The objective of this study is to analize of primiparous and multiparous knowledge identification about puerperal period. Design of this study was descriptive comparative studies. Population of respondents primiparous and multiparous in Puskesmas Jagir Surabaya of 40 people used techniques non probability sampling with purposive sampling approach as much as 36 respondents. Data analyze with Mann Whitney test p <0,05. Instrument research using questionnaire. The results showed primiparas who has good knowledge 4 (22.3%), insufficient knowledge as much as 6 people (33.3%), lack of knowledge of 8 (44.4%). While Multipara who has good knowledge of 9 (50.0%), insufficient knowledge of 7 (38.9%), lack of knowledge of two people (11.1%). Mann Whitney test results show the value of p = 0.024. So there is a difference between primiparous and Multiparous knowledge. Implication of this study is to provide new knowledge to the public about how to perform vulvar hygiene and public can contact the nearest health facility, so the nurses can provide appropriate education for healthy improve and welfare to primiparous and multiparous mothers. Keywords : Knowledge, primiparous and multiparous, Vulva Hygiene